Medea as a rape narrative: Edward Bond’s Dea - Gümüş Florentina; Biber, Vangölü Yeliz (The European journal of women's studies, 2025)
In contemporary theatre, the abundance of rape references reflects an unprecedented interest in revealing its ubiquity throughout history. The most recent triggering point for this growing interest may have been the beginning of the #MeToo movement in 2017; however, rape narratives have been the subject of theatre even before. One illustrative example is Edward Bond’s play Dea, a radical adaptation of Euripides’ Medea. What renders this play remarkable is that, although rape is not a feature of the ancient story, Bond places rape at the core of his adaptation. Through Julie Sanders and Linda Hutcheon’s theories of adaptation, as well as Lisa Fitzpatrick’s critical approach to the representation of rape in theatre, this essay explores the possible reasons for this transformation and how rape is related to a broader context of violence in the play.